User Knowledge Based on Big Data Analytics - Gribovskis, Justas (Information & Media, 2018)
[full article and abstract in Lithuanian; abstract in English]This article discusses the issues related to the interaction between big data and the new knowledge. A great deal of attention is paid to the development of new knowledge from big data analytics. The research scope of this article encompasses the largest telecommunications companies in Lithuania, which collect, process and adapt large amounts of data in their business environment. This new knowledge is related to the user and derives from the big data analysis, and it plays a very important role in today’s competitive environment. The study reveals that companies collect and process big data in order to get to know their customers (users) as much as possible. Today’s marketing would be impossible without big data analytics and the new knowledge gained from it.
Keywords: knowledge; new knowledge; knowledge management; big data; user knowledge; knowledge for the user; knowledge about the user; forecasting methods